An agent-based framework for secure and privacy-preserving personalized information services - Cissée, Richard; Rieger, Andreas; Braun, Nicolas; Albayrak, Sahin (Revista Colombiana de Computación, 2006)
Providers of next-generation ubiquitous services are facing increasing competition. In order to attract and satisfy customers, these services must offer added value e.g. by delivering personalized information in a seamless and multi-modal way. Personalized services, however, bring about additional requirements related to privacy and security, which have to be addressed if the services are to become widely accepted. Keywords: personalization, privacy, security, multi-agent systems, contextawareness.